Framing Analysis Media Kompas.com and CNNIndonesia.com: Vasectomy Program Discourse by Dedi Mulyadi - Baihaqi, Rizqi; Lestari, Hafsah Fauziah; Budiana, Nadila Radistya (Communication In Research And Publications, 2025)
The news regarding West Java Governor Dedi Mulyadi’s proposal to make vasectomy a prerequisite for receiving social assistance (bansos) sparked widespread public debate and was reported by various online media, including Kompas.com and CNNIndonesia.com. This issue is important to study because both media present contrasting narratives and perspectives about the same policy discourse. This study aims to analyze how Kompas.com and CNNIndonesia.com construct the reality of the vasectomy discourse using Robert N. Entman’s framing analysis model. Through a qualitative approach and textual analysis of news articles, this research explores four key framing elements: problem definition, cause diagnosis, moral judgment, and treatment recommendation. The results show that Kompas.com framed the issue as a controversy highlighting human rights violations and religious objections, thus portraying the proposal as unethical and discriminatory. Meanwhile, CNNIndonesia.com emphasized clarification from Dedi Mulyadi, presenting the issue as a misunderstood statement rather than an official policy, and adopting a neutral tone. These differences in framing reveal how media outlets shape public perception through selective emphasis and narrative construction.